Pengaruh Penerapan Model Pembelajaran Aktif, Kreatif, Efektif dan Menyenangkan (PAKEM) terhadap Keaktifan Siswa pada Mata Pelajaran Fiqih - Muhammad Nasrullah; Risnawati Risnawati; Fikri Hamdani (Journal on Education, 2024)
This study aims to analyze the relationship between the implementation of the Active, Creative, Effective, and Fun (PAKEM) Learning Model and student engagement in the Fiqh subject in grades VII, VIII, and IX at Madrasah Aliyah Pondok Pesantren Bahrul Ulum. A quantitative approach with a correlational method was used in this research. Data analysis was performed using correlation coefficients to measure the strength and direction of the relationship between the two variables under investigation. Data collection was conducted through classroom observation, where the PAKEM learning model was directly implemented, followed by the administration of a questionnaire to students. The results of the study show that the implementation of the PAKEM learning model increases student engagement by 53.6%. This finding affirms the effectiveness of the PAKEM model in encouraging active student participation. In contrast, if the PAKEM model is not applied, student engagement is predicted to decrease by 53.6%. The analysis revealed a significant relationship between the PAKEM learning model and student engagement, with an R square value of 0.553, indicating a "moderate" effect. Furthermore, the correlation coefficient of 0.743 shows a strong relationship between the two variables. These findings confirm that the PAKEM learning model has a significant impact on student engagement in Fiqh learning.